Treatment Persistence and Compliance with Medications for Chronic Obstructive Pulmonary Disease - Joyce A Cramer; Carole Bradley-Kennedy; Alissa Scalera (Canadian Respiratory Journal)
BACKGROUND AND OBJECTIVE: Inhaled beta-agonist, anticholinergic and glucocorticoid medications are used to treat asthma and chronic obstructive pulmonary disease (COPD). The present study assessed the patterns of persistence with the above mentioned inhaled medications.